Blockchain basics : a non-technical introduction in 25 steps - Drescher, Daniel (Apress, 2017)
In 25 concise steps, you will learn the basics of blockchain technology. No mathematical formulas, program code, or computer science jargon are used. No previous knowledge in computer science, mathematics, programming, or cryptography is required. Terminology is explained through pictures, analogies, and metaphors. This book bridges the gap that exists between purely technical books about the blockchain and purely business-focused books. It does so by explaining both the technical concepts that make up the blockchain and their role in business-relevant applications.- Resumé vydavatel
Keywords: šifrování dat; blockchain (technologie); data encryption; blockchain (technology); elektronické knihy; příručky; electronic books; handbooks and manuals